2016
DOI: 10.1177/0886260515580366
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence Experienced in the Sport Context by a Representative Sample of Quebec Adolescents

Abstract: This is the first study to report the prevalence of sexual violence perpetrated by a sport coach within a representative sample of the general population of adolescents aged between 14 and 17 years (N = 6 450). The questionnaire administered in high schools includes self-reported measures on a variety of dimensions relevant to the study of victimization, including sexual abuse, sexual contacts perceived as consensual, sexual harassment and involvement in an organized sport context. Descriptive and chi-square a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 22 publications
3
62
3
2
Order By: Relevance
“…178 Less commonly, athletes may even be sexually harassed or abused by a coach. 179 In a survey of Canadian adolescents, it was shown that 0.4% experienced sexual harassment and 0.5% were victims of sexual abuse at the hands of a coach, 180 and authors of an Australian analysis reported the prevalence of sexual abuse at a much higher 9.7%. 181 In the Canadian study, an additional 1.2% of athletes admitted to consensual sexual contact with a coach.…”
Section: Parental Influencementioning
confidence: 99%
See 1 more Smart Citation
“…178 Less commonly, athletes may even be sexually harassed or abused by a coach. 179 In a survey of Canadian adolescents, it was shown that 0.4% experienced sexual harassment and 0.5% were victims of sexual abuse at the hands of a coach, 180 and authors of an Australian analysis reported the prevalence of sexual abuse at a much higher 9.7%. 181 In the Canadian study, an additional 1.2% of athletes admitted to consensual sexual contact with a coach.…”
Section: Parental Influencementioning
confidence: 99%
“…181 In the Canadian study, an additional 1.2% of athletes admitted to consensual sexual contact with a coach. 180 Although there are no published estimates of abuse rates in US athletes, there have been numerous media reports of coachperpetrated sexual abuse in, among others, youth tennis, swimming, and martial arts in this country. [182][183][184] Sexual abuse of a child or teenager by a person in a position of trust (ie, coach) is a felony crime in every state.…”
Section: Parental Influencementioning
confidence: 99%
“…Young athletes are at risk of experiencing sexual maltreatment, physical maltreatment and psychological maltreatment in the context of practising their sport 7–13. Canadian veteran Olympic doctor and academic Dr Margo Mountjoy and colleagues14 argue that young athletes are particularly vulnerable to this form of violence due to the unique characteristics of the sport environment, such as the importance placed on the coach–athlete relationship, the intensity of youth sport, the demands of competition, the interest of the media in young athletes, time spent in distant training centres, recruitment procedures of young athletes, and the distance from home or school environment 14…”
Section: Introductionmentioning
confidence: 99%
“…Within sport sociology, sexual consent has only been briefly addressed, mainly regarding child athletes' inability to consent by drawing on sexual abuse cases (Brackenridge, 2001;Parent et al, 2015;Toftegaard-Nielsen, 2001). Yet, coach-athlete sexual relationships and sexual abuse occur among male and female athletes over and under the legal age of consent (Parent et al, 2015;Toftegaard-Støckel, 4 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within sport sociology, sexual consent has only been briefly addressed, mainly regarding child athletes' inability to consent by drawing on sexual abuse cases (Brackenridge, 2001;Parent et al, 2015;Toftegaard-Nielsen, 2001). Yet, coach-athlete sexual relationships and sexual abuse occur among male and female athletes over and under the legal age of consent (Parent et al, 2015;Toftegaard-Støckel, 4 2010). Ambiguity regarding coaches physical touch and interpersonal, intimate, and sexual behaviours in coach-athlete relationships abound and has been linked to sexual abuse (Bringer et al, 2002;Hassall, Johnston, Bringer, & Brackenridge, 2002;Toftegaard-Nielsen, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%